ESRA19-0656 Continuous erector spinae plane block with epidural catheter for post–operative analgesia following thoracic surgeries: a case series. (30th August 2019) - Ali, L; Farooq, A; Khan Raza, A; Taqi, A; Ali, I
Abstract : Background and aims: Erector spinae plane block (ESPB) is a novel regional analgesia technique for thoracic and abdominal surgeries. It can be employed for analgesia as an alternative to epidural block in patients presenting for thoracic surgeries. ESPB provides adequate analgesia, is technically easier to perform, and safer due to lower risk of serious complications as compared to epidural block. We illustrate this by presenting a case series of thoracic surgeries in which an ESPB was used for postoperative analgesia. We reviewed our SOP regarding use of continuous ESPB use for thoracic surgeries. Methods: 35 patients (ASA-III/IV) who underwent thoracic surgery (VATS, thoracotomy) under GA were included. Ultrasound-guided, 16-G epidural catheter was inserted at T5 level cephalo-caudally. 30 mL of 0.25% bupivacaine in ESPB administered prior to incision supplemented with Tramadol (1 mg/kg IV). Postoperatively ESPB infusion was started at 10 mL/h of 0.1% bupivacaine. the dose and catheter management in rooms/ward was done by anesthesia technicians. the outcomes assessed were number of hours in PACU stay, VAS 2 hourly in PACU and then 8 hourly in rooms/ward), safety profile and number of days of catheter in situ. Results: Mean VAS score in PACU was 3±2 and mean VAS score in room/ward was 1±1. Patient stay in PACU was for 8±4 hours. None of the patients had hypotension necessitating vasopressor support, and the catheter remained in situ for 4±2 days. Conclusions: Our case series reflects that ESPB provides adequate postoperative analgesia with no hemodynamic compromise in patients undergoing thoracic surgeries.